The Attitudes and Perceptions of Israeli Psychiatrists Toward Telepsychiatry and Their Behavioral Intention to Use Telepsychiatry - Kaphzan, Hanoch; Sarfati Noiman, Margaret; Negev, Maya (Frontiers in Psychiatry, 2022)
Background: Telepsychiatry is the use of communication technology to provide psychiatric services that can aid in overcoming a shortage of personnel. However, the service providers often hamper the assimilation and expansion of telepsychiatry, due to their attitudes and perceptions. The unified theory of acceptance and use of technology (UTAUT) is a model developed to assess the factors that influence the assimilation of new technology. Methods: An online questionnaire based on a modified UTAUT model was distributed among psychiatrists in Israel to examine the relationship between their attitudes and perceptions of telepsychiatry and their intention to use it. Seventy-six questionnaires were completed and analyzed. Results: The behavioral intention of Israeli psychiatrists to use telepsychiatry was relatively low, despite perceiving themselves as capable of high performance with low effort. Nonetheless, they were interested in using telepsychiatry voluntarily and held a positive attitude towards using telepsychiatry, and perceived its risk as average. Facilitating conditions and experience in telepsychiatry were found to positively affect the intention to use telepsychiatry, while the latter has the strongest effect. Overall, the modified UTAUT model explained ~40% of the variance in intention to use telepsychiatry. Discussion: Despite high-performance expectancy, low-effort expectancy, low perceived risk, a largely positive attitude, high voluntariness, and the expectancy for facilitating conditions, the intention to use telepsychiatry was rather low. This result is explained by low experience that plays a pivotal role. We recommend promoting the facilitating conditions when initiating telepsychiatry implementation and creating a sense of success during the initial stages of the experience.